Efficient biomass-endopolysaccharide production from an identified wild-Serbian Ganoderma applanatum strain BGS6Ap mycelium in a controlled submerged fermentation - Joshini Pillai Balamurugan; Sugenendran Supramani; Siti Rokhiyah Ahmad Usuldin; Zul Ilham; Anita Klaus; Nur Kusaira Khairul Ikram; Rahayu Binti Ahmad; Wan Abd Al Qadr Imad Wan-Mohtar (Elsevier Ltd., 2024)
Indexed by WOS/SCOPUS